The ghrelin system follows a precise post-natal development in mini-pigs that is not impacted by dietary medium chain fatty-acids - Boudry, Gaëlle; Cahu, Armelle; Romé, Véronique; Janvier, Régis; Louvois, Margaux; Catheline, Daniel; Rioux, Vincent; Le Huërou-Luron, Isabelle; Blat, Sophie (Frontiers in Physiology, 2022)
The ghrelin-ghrelin receptor (GHSR1) system is one of the most important mechanisms regulating food intake and energy balance. To be fully active, ghrelin is acylated with medium-chain fatty acids (MCFA) through the ghrelin-O-acetyl transferase (GOAT). Several studies reported an impact of dietary MCFA on ghrelin acylation in adults. Our study aimed at describing early post-natal development of the ghrelin system in mini-pigs as a model of human neonates and evaluating the impact of dietary MCFA. Suckled mini-pigs were sacrificed at post-natal day (PND) 0, 2, 5 and 10 or at adult stage. In parallel, other mini-pigs were fed from birth to PND10 a standard or a dairy lipid-enriched formula with increased MCFA concentration (DL-IF). Plasma ghrelin transiently peaked at PND2, with no variation of the acylated fraction except in adults where it was greater than during the neonatal period. Levels of mRNA coding pre-proghrelin (GHRL) and GOAT in the antrum did not vary during the post-natal period but dropped in adults. Levels of antral pcsk1/3 (cleaving GHRL into ghrelin) mRNA decreased significantly with age and was negatively correlated with plasma acylated, but not total, ghrelin. Hypothalamic ghsr1 mRNA did not vary in neonates but increased in adults. The DL-IF formula enriched antral tissue with MCFA but did not impact the ghrelin system. In conclusion, the ghrelin maturation enzyme PCSK1/3 gene expression exhibited post-natal modifications parallel to transient variations in circulating plasma ghrelin level in suckling piglets but dietary MCFA did not impact this post-natal development.